(Perservation of salted Press-Boiled Milk Fish (Chanos chanos) by Packaging Method) - Dwi Sutrisniati; Aan Yulistia; Juli Astuti (Balai Besar Industri Agro, 1987)
A study on the preservation of salted press-boiled (